Sexually transmitted infection risk behaviors in rural thai adolescents and young adults: Support for sex-and age-specific interventions - Amanda D. Latimore (2018)
Sexually transmitted infection (STI) prevalence and risks in a sample of rural Thai adolescents and young adults (14-29 years) were examined. Unprotected sex with a casual partner conferred the greatest risk for prevalent STIs, particularly for younger adolescents, and alcohol use increased the STI risk for women but not for men. © 2013 American Sexually Transmitted Diseases Association All rights reserved.